Evaluating the impact of green infrastructure on campus sustainability goals: A case study of universities in Bangkok - Kanchanawongpaisan, Sipnarong; Tee, Mcxin; Yangzhi, Min; Lu, Liangyan; Fang, Gao (Edelweiss Applied Science and Technology, 2025)
This study explores the impact of green infrastructure on the sustainability goals of universities in Bangkok by examining the roles of institutional support, environmental awareness, and sustainable behavior. The study involves a population comprising administrators, faculty, and students from government, autonomous, and private universities in Bangkok. Using Structural Equation Modeling (SEM), significant relationships among these variables were identified, alongside the moderating effect of stakeholders' perceived effectiveness of green infrastructure. Results reveal that institutional support strongly influences green infrastructure development, directly contributing to achieving campus sustainability goals. Environmental awareness significantly affects sustainable behavior, though an unexpected negative relationship was found between sustainable behavior and campus sustainability goals, highlighting a misalignment between individual practices and institutional metrics. Additionally, the perceived effectiveness of green infrastructure was found to have no significant moderating effect, suggesting that perceptions alone may not enhance sustainability outcomes. This research provides novel insights by addressing the contextual challenges of urban universities in Southeast Asia. It offers actionable recommendations for policymakers and administrators to align sustainable practices with measurable outcomes. Future research should explore alternative moderating variables, address the negative impact of sustainable behavior on sustainability goals, and conduct cross-regional studies for broader generalization.